Small tropical islands as hotspots of crustose calcifying red algal diversity and endemism - Mills, Matthew S.; Deinhart, Mari E.; Heagy, Mackenzie N.; Schils, Tom (Frontiers in Marine Science, 2022)
In the tropics, crustose calcifying red algae (Corallinophycidae and Peyssonneliales; CCRA) are dominant and important reef builders that serve a suite of ecological functions affecting reef health. However, CCRA taxa have historically been overlooked in floristic and ecological studies because of their high degrees of phenotypic plasticity and morphological convergence that impede reliable identifications based on morphology. This study provides an update of the CCRA diversity of Guam (Mariana Islands) based on a recent DNA barcoding effort. This account of CCRA taxa is compared to (1) the most current species inventories for Guam based on morphological identifications and (2) similar floristic accounts of CCRA from other regions using DNA barcoding. 492 CCRA specimens were collected from Guam for which two markers, COI-5P and psbA, were used for phylogenetic analysis and species delimitation. Phylogenetic relationships were inferred using maximum likelihood. Species richness estimates were obtained through a conservative approach using the Automatic Barcode Gap Discovery method for species delimitation. A total of 154 putative CCRA species were identified, with 106 representatives of the subclass Corallinophycidae and 48 belonging to the order Peyssonneliales. When compared to previous studies based on morphological identification, molecular data suggests that all but one of the CCRA species reported for Guam were incorrectly identified and CCRA species richness is more than six times higher than previously assumed. Species accumulation curves show that CCRA species richness will continue to rise with increased sampling effort and the exploration of new (micro)habitats before reaching a plateau. Guam’s true CCRA richness might eventually exceed the currently reported species richness of all marine red algae for the island. Of the 154 putative species documented in this study, only ten closely match (≥ 98% COI-5P sequence similarity) previously described species, implying that many are probably new species to science. The here-reported CCRA diversity for Guam as a small, remote tropical island in the Western Pacific Ocean is greater than those of well-documented CCRA floras for much larger nearshore ecosystems in Brazil and New Zealand, emphasizing the value of tropical islands as hotspots of marine biodiversity.